(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
A nation is built by its citizens and these citizens with their good health, hard work determines the future of a nation. To ensure a bright and prosperous future we need to focus on the health of a community. Community health is defined as simple services that are delivered by common men outside hospitals and clinics. Community health services can be classified into Preventive Health Services, Promotive Health Services, Curative Health Services, and Rehabilitative Health Services. Preventive health services include measures by which we can avoid the disease before its occurrence Dincharya, Ritucharya, Sadvrit, Tryoupstham, and Vegdharan can be included in this category. Similarly, promotive heath care services include Rasayan, Vaajikaran, Ashtaaharvidhi vishesh ayatan, Sadvrit, Tryoupstham. Curative health services include single-drug therapy for the different diseases called Ekal dravya and treatment of Kaas, Swash, Atisaar, Amlapita which are very common. Rehabilitative health services such as physical therapy, counseling, and other mental health services can be provided by Ashwashan chikitsa, Medhya rasaayan, Yoga, Pathya palan, Padansikkarm palan.